A world without innocence - TICKTIN, MIRIAM (American ethnologist, 2017)
What exactly is innocence—why are we morally compelled by it? Classic figures of innocence—the child, the refugee, the trafficked victim, and the animal—have come to occupy our political imagination, often aided by the important role of humanitarianism in political life. My goal is to see how innocence, a key ethico-moral concept, has come to structure what we think of as politics in the contemporary Euro-American context—how it maps political possibilities as well as impossibilities. The centrality of innocence to the political imagination is shaped by a search for a space of purity, one that constantly displaces politics to the limit of innocence and thereby renders invisible the structural and historical causes of inequality. We need, then, to open up political, moral, and affective grammars beyond innocence.